Dynamics of 5S rDNA in the tilapia (Oreochromis niloticus) genome: repeat units, inverted sequences, pseudogenes and chromosome loci - Martins, C.; Wasko, A. P.; Oliveira, C.; Porto-Foresti, F.; Parise-Maltempi, P. P.; Wright, J. M.; Foresti, F. (Karger, 2002)
In higher eukaryotes, the 5S ribosomal DNA (5S rDNA) is organized in tandem arrays with repeat units composed of a coding region and a non-transcribed spacer sequence (NTS). These tandem arrays can be found on either one or more chromosome pairs. 5S rDNA copies from the tilapia fish. Oreochromis niloticus, were cloned and the nucleotide sequences of the coding region and of the non-transcribed spacer were deter-mined. Moreover, the genomic organization of the 5S rDNA tandem repeats was investigated by fluorescence in situ hybridization (FISH) and Southern blot hybridization. Two 5S rDNA classes, one consisting of 1.4-kb repeats and another one with 0.5-kb repeats were identified and designated 5S rDNA type I and type II, respectively, An inverted 5S rRNA gene and a 5S rRNA putative pseudogene were also identified inside the tandem repeats of 5S rDNA type I. FISH permitted the visualization of the 5S rRNA genes at three chromosome loci, one of them consisting of arrays of the 5S rDNA type I, and the two others corresponding to arrays of the 5S rDNA type II. The two classes of the 5S rDNA. The presence of pseudogenes, and the inverted genes observed in the O. niloticus genome might be a consequence of the intense dynamics of the evolution of these tandem repeat elements. Copyright (C) 2002 S. Karger AG, Basel.